2009
DOI: 10.4322/rbpv.01803002
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown resistance in pyrethroid-resistant horn fly (Diptera: Muscidae) populations in Brazil

Abstract: To investigate the kdr (knockdown resistance) resistance-associated gene mutation and determine its frequency in pyrethroid-resistant horn fly (Haematobia irritans) populations, a total of 1,804 horn flies of 37 different populations from all Brazilian regions (North, Northeast, Central-West, Southeast, and South) were molecular screened through polymerase chain reaction (PCR). The kdr gene was not detected in 87.08% of the flies. However, the gene was amplified in 12.92% of the flies, of which 11.70% were res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 22 publications
2
10
0
Order By: Relevance
“…Flies survived twice the permethrin DC for 2 hours or even longer in most populations with survival rates greater than 1%, while no fly survived higher concentrations or longer exposures when the frequency of resistant individuals was lower than 1% (BARROS et al, 2007). Molecular analysis on some of these sampled populations confirmed that kdr (knockdown resistance) pyrethroid-resistant flies (SABATINI et al, 2009) were present in populations with permethrin RR as low as 1.5.…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations
“…Flies survived twice the permethrin DC for 2 hours or even longer in most populations with survival rates greater than 1%, while no fly survived higher concentrations or longer exposures when the frequency of resistant individuals was lower than 1% (BARROS et al, 2007). Molecular analysis on some of these sampled populations confirmed that kdr (knockdown resistance) pyrethroid-resistant flies (SABATINI et al, 2009) were present in populations with permethrin RR as low as 1.5.…”
Section: Resultsmentioning
confidence: 85%
“…Such negative cross-resistance has previously been reported in horn fly pyrethroid-resistant populations (SHEPPARD; MARCHIONDO, 1987;CROSBY et al, 1991), caused by increased diazinon activation by the mixed function oxidases (MFOs) that are present in pyrethroid-resistant flies (CILEK et al 1995). In fact, MFOs play the most important role in horn fly pyrethroid resistance in Brazil (ATM Barros, unpublished data), although kdr has been detected at low frequencies in pyrethroid-resistant populations (GUERRERO; SABATINI et al, 2009). The relatively low use of OP products for controlling horn flies, as well as the widespread pyrethroid resistance mainly due to oxidative metabolism, may explain the high OP susceptibility.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The kdr is already known in Brazilian pyrethroid-resistant horn fly populations (GUERRERO; BARROS, 2006;SABATINI et al, 2009), but little is known about its real importance and the role played by metabolic mechanisms.…”
Section: Introductionmentioning
confidence: 99%